2016
DOI: 10.5897/ajb2015.14680
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability of sorghum landraces from lower Eastern Kenya based on simple sequence repeats (SSRs) markers

Abstract: The aim of this study was to estimate the genetic variability of sorghum landraces grown in lower eastern Kenya based on simple sequence repeats (SSRs) markers. A total of 44 landraces obtained from the farmers and four improved varieties were analyzed using 20 SSR markers. All markers were polymorphic with polymorphism information content (PIC) value ranging from 0.04 to 0.81 with a mean of 0.49. Heterozygosity ranged from 0.00 to 0.04 suggesting that each detected a single genetic locus and that each of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 25 publications
1
1
1
Order By: Relevance
“…These markers do not vary much. Similar data were obtained by Barro-Kondombo et al (2010), Mbeyagala et al (2012) and Catherine et al (2016). The hypothetical K value obtained showed the three clusters in which the lines were embedded.…”
Section: Discussionsupporting
confidence: 82%
“…These markers do not vary much. Similar data were obtained by Barro-Kondombo et al (2010), Mbeyagala et al (2012) and Catherine et al (2016). The hypothetical K value obtained showed the three clusters in which the lines were embedded.…”
Section: Discussionsupporting
confidence: 82%
“…Similar findings by Cuevas and Prom ( 2013), and to a certain extent Agrama and Tuinstra (2003) also reported average PIC values 0.78 and 0.622, respectively. However, the observed PIC value is higher than that of Geleta et al (2006), Antoine et al (2015) and Catherine et al (2016) who reported 0.46, 0.33 and 0.49, respectively. This may be the result of low numbers of accessions considered in their studies and sample collections represented are from specific areas of agroecologies.…”
Section: Marker Polymorphismcontrasting
confidence: 65%
“…Qualitative and quantitative studies, in addition to RAPD, AFLP and SSR markers utilized by different scholars also revealed the same amounts of variations among their collections (Ayana and Bekele, 1998;Geleta et al, 2006;Cuevas and Prom, 2013). SSR marker studies from Eritrean, Eastern Kenya, Benin and Zambia collections also showed presence of wide genetic diversity of sorghum bicolor in Africa mainly in Eastern regions (Tesfamichael et al, 2014;Catherine et al, 2016;Antoine et al, 2015;Ng'uni et al, 2011). The existence of imbalanced sorghum races in the sample collections of the different studies from Ethiopia might contribute to the overall observed genetic variation (Cuevas and Prom, 2013).…”
Section: Introductionmentioning
confidence: 98%